Traditional Market Accounting: Management or Financial Accounting? - Wiyarni, Wiyarni (Asian Journal of Accounting Research, 2017)
The purpose of this study is to explore the area of accounting in traditional market. There are two areas of accounting: management and financial accounting. Some of traditional market traders have prepared financial notes, whereas some of them do not. Their financial notes usually consist of receivables, payables, customer orders, inventories, sales and cost price, and salary expenses. The purpose of these financial notes is usually for decision making. It is very rare for the traditional market traders to prepare financial notes for external users, such as vendors, creditors, and customers. This is because their transactions with vendors, creditors, and customers are very simple. This study used interpretive paradigm. Data was collected using in-depth interview and direct interaction with four informants from three traditional markets. Data is analyzed by organizing them, breaking them into manageable units, coding them, synthesizing them, and searching for patterns. Based on the analysis, this study found that the accounting area of traditional market activities is management accounting rather than financial accounting.